2014
DOI: 10.3109/00207454.2014.959121
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone's free radical scavenging mechanisms of neuroprotection against cerebral ischemia: review of the literature

Abstract: Free radicals and oxidative stress play key roles in cerebral ischemic pathogenesis and represent pharmacological targets for treatment. Edaravone (Edv), one of antioxidant agents that have been used in acute ischemic stroke in both clinical settings and animal experiments, exerts neuroprotective effect on ischemic injured brains. This review is aimed to elaborate the latest molecular mechanisms of the neuroprotection of Edv on cerebral ischemia and provide reasonable evidence in its clinical application. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 68 publications
0
25
0
1
Order By: Relevance
“…Neuronal protective effects of Edaravone against ischemia–reperfusion injury have been intensively studied in cell models, animal models, and clinical trials. It is closely related to the facets of scavenging reactive oxygen species (ROS), hydroxyl radical (OH), and RNS . Recently, several molecular pathways have been shown to mediate hypoxia sensing at the cellular and molecular levels.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal protective effects of Edaravone against ischemia–reperfusion injury have been intensively studied in cell models, animal models, and clinical trials. It is closely related to the facets of scavenging reactive oxygen species (ROS), hydroxyl radical (OH), and RNS . Recently, several molecular pathways have been shown to mediate hypoxia sensing at the cellular and molecular levels.…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals are important in long term ischemia as well (1). It is indicated that free radicals contribute to brain lesions and ischemia-induced free radical damage (15,16). MCAO gives rise to the increased intracellular calcium and excessive free radicals.…”
Section: +mentioning
confidence: 99%
“…This condition of oxidative stress in the highly vulnerable brain tissue leads to lipid peroxidation, protein oxidation, different types of DNA damage, and eventually to neuronal cell death. In this sense, antioxidants of varying chemical structures have been investigated as therapeutic agents in the treatment of this acute injury (Alonso-Alconada et al, 2013; Ren et al, 2015).…”
Section: Introductionmentioning
confidence: 99%